2023
DOI: 10.1101/2023.04.05.535790
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Applications of Boolean modeling to study the dynamics of a complex disease and therapeutics responses

Abstract: Computational modeling has emerged as a critical tool in investigating the complex molecular processes involved in biological systems and diseases. In this study, we apply Boolean modeling to uncover the molecular mechanisms underlying Parkinson's disease (PD), one of the most prevalent neurodegenerative disorders. Our approach is based on the PD-map, a comprehensive molecular interaction diagram that captures the key mechanisms involved in the initiation and progression of PD. Using Boolean modeling, we aim t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 91 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…1. Differentially expressed genes in two datasets describing the PINK1 Q456X and GBA N307S mutations in T2DM were identified and common overlaps with the genes in the substantia nigra dataset on the PD Map were determined [11]. It was found that 81 genes are commonly altered across datasets (see the Suplementary File) 2.…”
Section: Rnaseq Data Analysis For T2dm Comorbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…1. Differentially expressed genes in two datasets describing the PINK1 Q456X and GBA N307S mutations in T2DM were identified and common overlaps with the genes in the substantia nigra dataset on the PD Map were determined [11]. It was found that 81 genes are commonly altered across datasets (see the Suplementary File) 2.…”
Section: Rnaseq Data Analysis For T2dm Comorbiditymentioning
confidence: 99%
“…PBNs enable us to simulate the impact of molecular dysregulation, thus providing more understanding of the disease pathways. This approach is particularly effective in exploring the complexities of PD pathways and their variations across different disease subtypes [11,12].…”
Section: Introductionmentioning
confidence: 99%